Medication use process and assessment of extemporaneous compounding and alternative routes of administration of oral oncology drugs: Guidance for clinical and oncology pharmacists. Issue 11 (12th September 2022) - Cohen, Jonathan; Lee, Christopher; Markham, Ryan; Szerwo, James; Roska, Mark; Bubalo, Joseph
Abstract: Cancer treatment is evolving. Oral formulations offer potentially more convenient, effective alternatives to conventional chemotherapy for many cancers. An appealing aspect of oral antineoplastic agents is their relative ease of administration; unfortunately, patients may have difficulty swallowing the tablets or capsules. This shift towards oral administration and the accompanying issues around oral medication adherence highlights the need to assess the safety and feasibility of delivery methods for patients unable to swallow solid dosage forms. A new medication‐use process (MUP) was created to facilitate extemporaneous compounding of oral oncology drugs (OOD). Systematic review consisting of tertiary resources, drug manufacturers, and primary literature was performed to identify information related to extemporaneous compounding or alternative routes of administration for a predetermined list of OODs. A single‐center retrospective review was conducted of patients receiving liquid formulations of OODs to characterize institutional experience. Overall, 116 OODs were reviewed. The majority of OODs had information describing extemporaneous compounding or alternative routes of administration (31% with commercial liquid formulations available or information in tertiary resources; 33% with off‐label manufacturer information or case reports) while 36% had no data. The MUP included three compounding workflows to account for available solid dosage formulations (tablet, hard capsule, gelatin capsule) and creation of an electronic health record order template. Retrospective review identified 41 patients who received compounded liquid formulations of 14 OODs for 13 indications. Liquid OODs were used for a median of 3‐5 days. None of the 41 patients experienced discernable safety or overt effectiveness concerns readily attributed to use of liquid OODs. Implementation of a novel MUP and systematic review of OODs aids the pharmacist in standardizing institutional practice and mitigates risks associated with extemporaneous liquid formulations of OODs facilitating medication delivery of new agents to patients unable to swallow solid dosage forms.